Mola vesicular treatment by pituitrin and curettage - Bazul, Víctor (2015)
A detailed clinically study of 14 of Hydatidiform Mole has been reported. The diagnosis was made clinically and by Galli Mainini test. Toxemias of pregnancy was predominant in five cases. with a serious and poor condition of the patients. In the other nine cases the hemorrhage was profuse and acute Anemia has been established. One of them died by this condition. Ten were multiparas, the other four were primiparas. As soon as the diagnosis is made the uterus must be emptied. In most instances this can be accomplished easily by dilatation with Hegar dilators followed by curettage. Curette and placenta forceps should be used with the utmost caution because of the danger of perforating the uterus. In any case the curettage should be associated with pituitary extraer and ergonovine. The patients was kept under close observation by a long time -no less of two years- and no anyone developed chorionepithelioma.